This study was carried out in the Plant Virology Laboratory belonging to the Plant Protection Department at the Faculty of Agriculture-Karbala University with the aim of isolation and molecular identification of five fungi, isolated from the roots of some - Barbar, Aqeel Nazzal; Abu-Duka, Ahmed B.; AL-Ghazali, Noor A. AL-Ghazali A.; Ali, Amel A. (Journal of Kerbala for Agricultural Sciences, 2018)
This study was carried out in the Plant Virology Laboratory belonging to the Plant Protection Department at the Faculty of Agriculture-Karbala University with the aim of isolation and molecular identification of five fungi, isolated from the roots of some tomato plants growing in the plastic tunnels located in a desert region in Karbala governorate during the agricultural season 2017-2016, using the polymerase chain reaction (PCR) technique and determining the sequences of nitrogen bases of PCR products amplified by the universal primers ITS1 and ITS4. Results, obtained from the PCR amplification and analysis of the sequences of nitrogen bases of PCR-amplified products using BLAST program (Basic Local Alignment Search Tool), showed that the identified isolates are belonged to the fungi Rhizoctonia solani, F. verticilliodes, F. solani and P. tardochrysogenum. From the comparison of the sequences of nitrogen bases obtained from the identified fungal isolates with those available at the National Center for Biotechnology Information (NCBl), it was revealed that the identified fungi R. solani and P. tardochrysogenum were not previously recorded at NCBI, therefore; the identified sequences of these fungi have been deposited and recorded in GenBank database (NCBI) under the accession numbers: KX255861and KX555634.